1991
DOI: 10.1161/01.res.69.2.313
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of thromboxane A2 synthase inhibition, singly or combined with thromboxane A2/prostaglandin endoperoxide receptor antagonism, on occlusive thrombosis elicited by endothelial cell injury or by deep vascular damage in canine coronary arteries.

Abstract: In open-chest dogs, cyclic flow reductions (CFRs, 5.1-6.6/hr in controls; n = 24) caused by platelet deposition/dislodgment at sites of endothelial cell injury in critically stenosed left anterior descending coronary arteries (59% flow reduction) were attenuated to the same extent either by single thromboxane A2 (TXA2) synthase inhibition (0.31 mg/kg i.v. ridogrel; CFR, 0.16 +/- 0.16/hr; n = 6; p less than 0.05) or by a comparatively modest degree of TXA2/prostaglandin endoperoxide receptor antagonism on top o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…However, such a low grade antagonism of TXA 2 /PG endoperoxide receptors when superimposed on a strong reduction of TXA 2 synthase activity may produce substantial functional effects. That possibility is corroborated by the anti-platelet activity of ridogrel at dual acting doses, stronger than that of either single TXA 2 synthase or TXA 2 /PG endoperoxide receptor antagonism, in preventing coronary thrombosis, speeding up rt-PA thrombolysis and preventing re-occlusion after successful lysis in animal models (7,21,47,49).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, such a low grade antagonism of TXA 2 /PG endoperoxide receptors when superimposed on a strong reduction of TXA 2 synthase activity may produce substantial functional effects. That possibility is corroborated by the anti-platelet activity of ridogrel at dual acting doses, stronger than that of either single TXA 2 synthase or TXA 2 /PG endoperoxide receptor antagonism, in preventing coronary thrombosis, speeding up rt-PA thrombolysis and preventing re-occlusion after successful lysis in animal models (7,21,47,49).…”
Section: Discussionmentioning
confidence: 96%
“…However, specific inhibition of the TXA 2 synthase produces an accumulation of PG endoperoxides, activating platelet and vascular TXA 2 /PG endoperoxide receptors and attenuating the inhibitory effects of PGI 2 and PGD 2 . Therefore, a combination of TXA 2 synthase inhibition and of TXA 2 /PG endoperoxide receptor antagonism has been advocated as an improved pharmacological maneuver against platelet-dependent thrombus formation (7,14,16,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…While this hypothesis remains to be studied directly, similar conclusions were reached by Vandeplassche el al. (28), who demonstrated that prevention of arterial occlusion following deep vascular injury required a higher dose of ridogrel (a thromboxane synthase inhibilor/receplor antagonist) than that needed for prevention of platelet-dependent cyclic coronary flow reductions. These investigators suggested that the higher dose of ridogrel would be expected to result in greater platelet concentrations of cAMP and, hence, antithrombotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, specific inhibitors of TXA 2 synthase are also responsible for increasing generation of prostanoids such as prostaglandin I 2 , which can be beneficial by attenuating platelet activation and decreasing vascular resistance. Therefore, efforts to modulate the actions of TXA 2 focused on agents able to block biosynthesis of TXA 2 and to antagonize both PGH 2 and TXA 2 at their common receptor (Oates et al, 1988;Vandeplassche et al, 1991;Vandeplassche et al, 1993).…”
Section: Introductionmentioning
confidence: 99%